COPING STRATEGIES OF HUSBAND VIOLENCE AGAINST WIVES: A LITERATURE REVIEW - Dulce Elda Ximenes dos Reis (State Islamic University (UIN) Ar-Raniry, 2021)
Violence is a major societal problem around the world violence, against women includes domestic violence which is usually the wife who is the victim, as the results of WHO (2012) study of more than 24,000 women in 10 countries, from various cultures, geographies and urban / rural areas. Research in 50 countries, shows that between 10 - 60% of women who have been married or partnered have experienced physical violence from their partners. This research method uses a literature review analysis research technique. The results of the systematic review conducted by the author contained 40 journals and then selected by the authors, only 4 journals were retained by the authors. The results of the journal analysis show that the majority of women victims of domestic violence use PFC that is tailored to existing problems, namely seeking assistance from formal and non-formal institutions to help them overcome the problems they experience.